2012
DOI: 10.2105/ajph.2012.300679
|View full text |Cite
|
Sign up to set email alerts
|

Primary Care and Public Health Activities in Select US Health Centers: Documenting Successes, Barriers, and Lessons Learned

Abstract: Lessons learned from health centers should inform strategies to better integrate public health with primary care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
32
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 7 publications
1
32
0
Order By: Relevance
“…As a part of that effort, 2 authors (LCW and MDL) analyzed the overlap between program components and PCMH elements, which is shown in Table 1. 14 We also analyzed the program using the Local Public Health System Performance Assessment Instrument 16 (version 2.0) to characterize the manner in and degree to which the program is meeting the performance standards set forth in the "10 Essential Public Health Services" 15 (Table 2). Following the example of Lebrun, 4 we assigned Likert values to each of the 10 essential services to represent the level to which each activity/standard named in the assessment is accomplished in our partnership (0 ϭ not accomplished, 1 ϭ minimally accomplished, Physician-directed medical practice A family physician is the medical director of PTH-PA.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a part of that effort, 2 authors (LCW and MDL) analyzed the overlap between program components and PCMH elements, which is shown in Table 1. 14 We also analyzed the program using the Local Public Health System Performance Assessment Instrument 16 (version 2.0) to characterize the manner in and degree to which the program is meeting the performance standards set forth in the "10 Essential Public Health Services" 15 (Table 2). Following the example of Lebrun, 4 we assigned Likert values to each of the 10 essential services to represent the level to which each activity/standard named in the assessment is accomplished in our partnership (0 ϭ not accomplished, 1 ϭ minimally accomplished, Physician-directed medical practice A family physician is the medical director of PTH-PA.…”
Section: Methodsmentioning
confidence: 99%
“…Primary care and patient-centered medical homes (PCMHs) can play a significant role in helping to meet public health needs. 3,4 This article offers an example of this process, in which an extended PCMH in the Thomas Jefferson University Department of Family and Community Medicine (DFCM) and a local nonprofit Housing First agency, Pathways to Housing-PA (PTH-PA), have partnered successfully to better meet the individual and population health needs of formerly homeless people with SMI. Through a fusion of a PCMH model with elements of community-oriented primary care and a public health outreach, a unique and synergistic community of solution emerged.…”
mentioning
confidence: 99%
“…By mapping the classification schemes in our 11 included works (representing 9 unique studies) to the Jorm et al classes, 13 we found the use of "methods" in seven unique studies 1,[6][7][8][9][10]14,26,27 "health issues" in four, 6,8,9,11,14,28 "resources and infrastructure" in four, 6,8,10,28 "functions" in two, 1,6 "settings" in two, 6,7 and "determinants of health" in none. Beyond the Jorm et al classifications, 13 "target population, " which four studies described, 6,8,9,14 and "organization type, " 1,6,8,10,28 as distinct from intervention setting, emerged as potentially important domains.…”
Section: Taxonomy Of Integration Interventionsmentioning
confidence: 99%
“…The review and the scan identified and synthesized 49 interventions. 27 This study of nine federally qualified health centers examined primary care and public health activities to better understand their successes, barriers encountered, and lessons learned. Lebrun et al used qualitative and quantitative methods to collect data, including secondary data from the Uniform Data System, questionnaires, and key informant interviews.…”
Section: Sloane Et Al (2009) 10mentioning
confidence: 99%
“…5,6 However integration is defined, the literature seems fairly consistent in calling for coordinated infrastructure and funding; shared vision, mission and values; alignment of goals and objectives; alignment of leadership; partnership; sustainability, evaluation; community engagement; shared data and analysis; contextual variables; and innovation. 8,[11][12][13][14][15][16][17][18][19] Although this literature comprehensively describes models of interaction between PC and PH, more could be done to learn how both partners experience or prioritize such aspects of at the local level, and in a way that considers the processes or actions that can support successful implementation. 20 -22 In this study, PC and PH practice-based research networks (PBRNs) from 4 states came together to explore the continuum of integration proposed by the IOM (eg, mutual awareness, cooperation, collaboration, partnership), 7 examine the dimensions of integration on this continuum, and identify factors that facilitate or impede integration.…”
mentioning
confidence: 99%